2015
DOI: 10.1007/s00132-015-3141-9
|View full text |Cite
|
Sign up to set email alerts
|

Osteomalazie und Vitamin-D-Hypovitaminose

Abstract: In addition to the recording of symptoms and medical imaging, the diagnosis of osteomalacia should be ensured by laboratory parameters. Adequate treatment consists of the high-dose intake of vitamin D3 and the replacement of phosphate if deficient. Vitamin D is one of the important hormone-like vitamins and is required in all human cells. Deficiency of vitamin D has far-reaching consequences not only for bone, but also for other organ systems.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
15
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(15 citation statements)
references
References 9 publications
0
15
0
Order By: Relevance
“…Moreover, several studies have also shown a relationship between musculoskeletal pain (e.g., low-back pain) and serum vitamin D level [34][35][36][37][38][39]. Among these studies, a cross-sectional study performed in Norway, including 572 patients with musculoskeletal pain, headaches or fatigue, concluded that more than half of all those subjects suffering from pain (58%) showed vitamin D levels < 50 nmol/L [40].…”
Section: Vitamin Dmentioning
confidence: 99%
“…Moreover, several studies have also shown a relationship between musculoskeletal pain (e.g., low-back pain) and serum vitamin D level [34][35][36][37][38][39]. Among these studies, a cross-sectional study performed in Norway, including 572 patients with musculoskeletal pain, headaches or fatigue, concluded that more than half of all those subjects suffering from pain (58%) showed vitamin D levels < 50 nmol/L [40].…”
Section: Vitamin Dmentioning
confidence: 99%
“…In 1997, the recommended daily allowance for vitamin D intake to prevent a deficiency was 5 μg (200 IU) from childhood onwards up to late adulthood (50 years of age), 10 μg (400 IU) for people aged 50–70 years, and 15 μg (600 IU) for those over 70 years of age [ 6 ]. In presence of an osteomalacia, the weekly intake recommended by current guidelines should be much higher (20,000 to 40,000 IU/week) [ 42 ]. The necessary daily doses of vitamin D to prevent falls have been reported to be between 700 and 1000 IU [ 43 ].…”
Section: Vitamin D—prevalence Of Deficiency and Insufficiencymentioning
confidence: 99%
“…Osteomalacia, another metabolic bone disease mainly caused by malfunction of the vitamin D or phosphate metabolism, leads to a reduced bone mineralization in adults [ 12 , 42 ]. Unlike rickets, osteomalacia is rare in children [ 8 ].…”
Section: Bone Healthmentioning
confidence: 99%
See 1 more Smart Citation
“…Although all other biochemical indices, except vitamin D, were within normal range, osteomalacia in the hip area must be assumed in the clinical scenario of insufficient bilateral femur neck fracture. [ 8 ]…”
Section: Discussionmentioning
confidence: 99%